Visualisasi Data Persentase Penduduk Miskin pada Pulau Kalimantan Indonesia Tahun 2019 - 2024 Menggunakan Microsoft Excel - Dwiva Krisnoprianto Pratama; Christian Fedrik Nakano; Jadiaman Parhusip (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
This article discusses the issue of poverty in Kalimantan Island, Indonesia, with a focus on the analysis of poverty data from 2019 to 2024. Despite Kalimantan's wealth of natural resources, economic disparities and uneven distribution remain significant challenges. This research uses data from the Central Statistics Agency (Badan Pusat Statistik) to demonstrate the impact of the COVID-19 pandemic, which caused an increase in the number of people living in poverty due to income reductions and job losses. By utilizing Microsoft Excel, data visualization is employed to present information clearly and concisely, making it easier to understand the poverty situation in the region. The findings of this research recommend that poverty alleviation policies be more focused and data-driven, and encourage further research to understand the factors influencing poverty. It is hoped that this article will provide valuable insights for the development of policies and poverty alleviation efforts in Indonesia, particularly in Kalimantan Island.